Áreas de preservação permanente fluviais na área de proteção ambiental do córrego Timburi, município de Presidente Prudente-SP - Gonçalves, Thais Helena [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work sought to study Permanent Preservation Areas (APP) of the Environmental Protection Area (APA) of the Timburi Stream regarding the remaining vegetation and propose ecological restoration for a degraded stretch. After analyzing the Permanent Preservation Areas, the ecological restoration proposal took place on a rural property. The chosen rural property is located to the west of APA Timburi, in the municipality of Presidente Prudente, state of São Paulo. The option for this study area was due to its geographic location and importance, since the area is part of the Timburi Environmental Protection Area (APA), recently created by the Supplementary Law of the Municipality of Presidente Prudente no 235/2019. In order to understand the physical aspects of the Environmental Protection Area (APA) of Timburi, cartographic products of hypsometry, slope, geology, geomorphology and land use and coverage (year 2020) were generated. The area of permanent preservation in the APA and land use and coverage in the APP were also mapped, using radar images from the Topographic Mission Radar Shuttle (SRTM / NASA, 2000) and, respectively, satellite images from the LANDSAT 8 series of the 25/03/03 / 2020. Through the interpretation of the satellite images, APPs with forest cover were identified, and the sections with conflict of use (degraded), allowing their diagnosis. Later, through field trips, adjustments, detailing and verification of the elements identified in the satellite images were possible. Field work was essential to determine the degraded APP stretches that would need ecological restoration, as well as the identification of disturbance factors. Restoration measures have been proposed for a rural property, such as the isolation of disturbance factors and planting of seedlings to restore the native forest, in order to protect the water resource, soil and other environmental aspects present there. In view of the advances in the use of ecological restoration techniques in recent years, as an alternative for the recovery of degraded ecosystems and environmental balance, we seek to show that it can be done using simple techniques that guarantee a good result over the years.

Este trabalho buscou estudar Áreas de Preservação Permanente (APP) da Área de Proteção Ambiental (APA) do Córrego Timburi quanto a vegetação remanescente e propor restauração ecológica para um trecho degradado. Após a análise das Áreas de Preservação Permanente a proposição de restauração ecológica ocorreu em uma propriedade rural. A propriedade rural escolhida, localiza-se a oeste da APA Timburi, município de Presidente Prudente, estado de São Paulo. A opção por essa área de estudo ocorreu pela localização geográfica e importância, visto que a área faz parte Área de Proteção Ambiental (APA) do Timburi, recém criada pela Lei Complementar do Município de Presidente Prudente no 235/2019. Para a compreensão dos aspectos físicos da Área de Proteção Ambiental (APA) do Timburi foram gerados produtos cartográficos de hipsometria, declividade, geologia, geomorfologia e uso e cobertura da terra (ano 2020). Também foram mapeadas a área de preservação permanente na APA e uso e cobertura da terra na APP, utilizando imagens de radar da Missão Topográfica Radar Shuttle (SRTM/NASA, 2000) e respectivamente imagens de satélite da série LANDSAT 8 do dia 25/03/2020. Por meio da interpretação das imagens de satélite foram identificadas as APP com cobertura florestal, e os trechos com conflito de uso (degradadas), permitindo o diagnóstico das mesmas. Posteriormente, por meio de idas a campo foram possíveis ajustes, detalhamento e verificação dos elementos identificados nas imagens de satélite. Os trabalhos de campo foram essenciais para a determinação dos trechos de APP degradadas que necessitariam de restauração ecológica, bem como a identificação dos fatores de pertubação. Foram propostas medidas de restauração para uma propriedade rural, como o isolamento dos fatores de perturbação e plantio de mudas para recompor a mata nativa, visando proteger o recurso hídrico, solo e os demais aspectos ambientais ali presentes. Diante do avanço da utilização de técnicas de restauração ecológica nos últimos anos, como alternativa para a recuperação de ecossistemas degradados e equilíbrio ambiental, busca-se mostrar que ela pode ser feita a partir de técnicas simples que garantem um bom resultado ao longo dos anos.
Permanent fluvial preservation areas in the Timburi stream environmental protection area, municipality of Presidente Prudente-SP
Keywords: Permanent preservation area; Ecological restoration; Timburi environmental protection area; Área de preservação permanente; Restauração ecológica; Área de proteção ambiental do Timburi